Struktur dan Nilai Pendidikan Karakter dalam Novel Teruslah Bodoh Jangan Pintar Karya Tere Liye - Krisyadi Dwi Sukma; Imas Juidah; Eli Herlina; Saroni Saroni (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The novel Teruslah Bodoh Jangan Pintar by Tere Liye is one of the novels that has many readers in Indonesia. This study aims to describe the structure and educational values in the novel Teruslah Bodoh Jangan Pintar by Tere Liye. This research uses qualitative method. The data in this study are in the form of sentences in the novel Teruslah Bodoh Jangan Pintar by Tere Liye. The data source in this research is Teruslah Bodoh Jangan Pintar by Tere Liye. The result of this research shows that Teruslah Bodoh Jangan Pintar by Tere Liye has an intact structure as a novel. The structure includes theme, plot, characterisation, setting, language style, point of view, and mandate. Furthermore, the novel Teruslah Bodoh Jangan Pintar by Tere Liye also contains educational values such as the value of loving the environment, honest value, empathy value, responsibility value, courage value, and critical thinking value. Thus, the novel Teruslah Bodoh Jangan Pintar by Tere Liye can be used as an alternative teaching material in schools.